The Social Ties of the Parish Priest, Provost, and Archdeacon Valentin Fabri, an Ambitious Commissioner of Construction Works - Žnidaršič Golec, Lilijana (Acta historiae artis Slovenica, 2022)
Valentin Fabri was one of the most prominent priests of the last fifth of the 15th and the first decade of the 16th century in Slovenia. He was parish priest in Slovenske Konjice and archdeacon of the Savinja Archdeaconate, parish priest in Vuzenica, as well as provost in Dobrla vas (Eberndorf) and archdeacon in Podjuna (Jauntal) from 1497 until his death in 1509. Under his leadership, reconstructions took place in the parish churches of Konjice and Vuzenica, while in the chapter church in Dobrla vas construction works continued. While Matej Klemenčič has analysed Fabri’s engagement in construction works from the art-historical perspective, the present discussion focuses on his social ties, established in his home environment in Konjice, during his studies in Vienna (and probably elsewhere), as well as during his entire career. The identification of the people associated with Fabri, based on the relevant sources, can be a useful starting point for further discussions of Fabri’s construction activities. Among the persons who are also interesting in the broader historiographical sense, the aristocrats from the ranks of the former clientele of the Counts of Celje/Cilli and the members of the higher clergy stand out.